CTNI-38. UPDATE ON GBM AGILE: A GLOBAL, PHASE 2/3 ADAPTIVE PLATFORM TRIAL TO EVALUATE MULTIPLE REGIMENS IN NEWLY DIAGNOSED AND RECURRENT GLIOBLASTOMA. (14th November 2022) - Buxton, Meredith; Alexander, Brian; Berry, Donald; Cavenee, Webster; Colman, Howard; de Groot, John; Ellingson, Benjamin; Gordon, Gary; Khasraw, Mustafa; Lassman, Andrew; Lee, Eudocia; Li, Wenbin; et al.
Abstract: BACKGROUND: GBM AGILE (Glioblastoma Adaptive, Global, Innovative Learning Environment) is a biomarker based, multi-arm, international, seamless Phase 2/3 response adaptive randomization platform trial designed to rapidly identify experimental therapies that improve overall survival and confirm efficacious experimental therapies and associated biomarker signatures to support new drug approvals and registration. GBM AGILE is a collaboration between academic investigators, patient organizations and industry to support new drug applications for newly diagnosed and recurrent GBM. METHODS: The primary objective of GBM AGILE is to identify therapies that effectively improve the overall survival in patients with ND or recurrent GBM. Bayesian response adaptive randomization is used within subtypes of the disease to assign participants to investigational arms based on their performance. Operating under a Master Protocol, GBM AGILE allows multiple drugs from different pharmaceutical/biotech companies to be evaluated simultaneously and/or over time against a common control. New experimental therapies are added as information about promising new drugs is identified while therapies are removed as they complete their evaluation. The master protocol/ trial infrastructure includes efficiencies through an adaptive trial design, shared control arm and operational processes to serve the goal of helping patients receive optimal care in a fast and efficient manner. GBM AGILE has screened over 1200 patients and enrollment rates are 3 to 4 times greater than traditional GBM trials, with active sites averaging 0.75 to 1 patients/sites/month. There are 41 active sites in the US, 4 active sites in Canada and 3 active sites in Europe with more sites anticipated to open across 5 countries in Europe. Expansion to China and Australia are under progress. Through the use of improved and flexible processes, GBM AGILE serves as a global trial that supports the efficient and rapid incorporation and evaluation of new experimental therapies for patients with GBM.Clinical trial information: NCT03970447.